Rehabilitation of basketball injuries - Malanga, G. A.; Chimes, G. P. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
Basketball is one of the most popular sports in the United States and throughout the world, and therefore represents one of the most common sources of sports-related injuries. Basketball injuries should be managed by the same general rehabilitation principles as other sports injuries. Additionally, the clinician should be aware not only of general sports injuries but of those injuries most commonly seen in basketball players. By maintaining knowledge of the most common basketball injuries as well as their diagnosis and treatment, the clinician can help to optimize the athlete's return to play and enjoyment of the sport.